This action might not be possible to undo. Are you sure you want to continue?

# BOOLEAN ALGEBRA AND LOGIC GATES

BOOLEAN ALGEBRA

An algebraic system developed by George Boole in 1854. In 1938, C. E. Shannon introduced a twovalued Boolean algebra called Switching algebra that represented the properties of bistable electrical switching circuits.

**FORMAL DEFINITION OF BOOLEAN ALGEBRA
**

Boolean algebra is an algebraic structure defined by a set of elements, B, together with two binary operators, + and , provided that the following postulates (formulated by E. V. Huntington in 1904) are satisfied: 1. (a) The structure is closed with respect to the operator +. (b) The structure is closed with respect to the operator . 2. (a) The element 0 is an identity element with respect to +; that is, x + 0 = 0 + x = x. (b) The element 1 is an identity element with respect to ; that is, x 1 = 1 x = x.

5. y B such that x y. For every element x B. x + y = y + x. There exist at least two elements x. (a) The structure is commutative with respect to +. that is. (b) The structure is commutative with respect to . . 6. x ( y + z ) = ( x y) + (x z ). 4.3. that is. (b) The operator + is distributive over . x y = y x. x + ( y z ) = ( x + y ) ( x + z ). that is. that is. there exists a element x¶ B (called complement of x) such that (a) x + x = 1 and (b) x x = 0. (a) The operator is distributive over +.

TWO-VALUED BOOLEAN ALGEBRA Defined on a set of two elements. with rules for the two binary operators + and x 0 0 1 1 y 0 1 0 1 x y 0 0 0 1 x 0 0 1 1 y 0 1 0 1 x+y 0 1 1 1 x 0 1 x' 1 0 .1}. B = {0.

± If the dual of an algebraic expression is desired. .BASIC THEOREMS AND PROPERTIES OF BOOLEAN ALGEBRA DUALITY PRINCIPLE ± States that every algebraic expression deductible from the postulates of Boolean algebra remains valid if the operators and identity elements are interchanged. we may simply interchange OR and AND operators and replace 1 s by 0 s and 0 s by 1 s.

absorption (a) (a) (a) (a) x+0 = x x+x = 1 x+x = x (b) (b) (b) (b) x 1=x x x =0 x x=x x 0=0 (a) x+1 = 1 (x ) = x x + y = y+ x (b) (b) xy = yx x ( yz ) = ( xy ) z (a) x + ( y + z ) = ( x + y ) + z (a) (a) (a) x ( y + z ) = xy + xz (x+y) = xy x + xy = x (b) x + ( yz ) = ( x + y ) ( x + z ) (b) ( xy ) = x + y (b) x ( x + y ) = x . commutative Theorem 4. distributive Theorem 5. THEOREMS must be proven from the postulates. DeMorgan Theorem 6. Postulate 2 Postulate 5 Theorem 1 Theorem 2 Theorem 3. associative Postulate 4. involution Postulate 3.POSTULATES AND THEOREMS OF BOOLEAN ALGEBRA POSTULATES basic axioms of the algebraic structure and need no proof.

THEOREM 1(a): x + x = x Statement Justification x+x =(x+x) 1 postulate 2(b) =(x+x) (x+x) 5(a) = x + xx 4(b) =x+0 5(b) =x 2(a) .

THEOREM 1(b): x x = x Statement Justification x x = xx + 0 postulate 2(a) = xx + xx 5(b) =x(x+x) 4(a) =x 1 5(a) =x 2(b) NOTES: Theorem 1(b) is the dual of theorem 1(a) and each step of the proof is the dual of its counterpart in part (a). . Any dual theorem can be similarly derived from the proof of its corresponding theorem.

THEOREM 2(a): x + 1 = 1 Statement Justification x + 1 = 1 ( x + 1) postulate 2(b) = ( x + x ) ( x + 1) 5(a) =x+x 1 4(b) =x+x 2(b) =1 5(a) THEOREM 2(b): x 0 = 0 by duality. .

THEOREM 6(a): x + xy = x Statement x + xy = x 1 + xy =x(1+y) =x(y+1) =x 1 =x Justification postulate 2(b) 4(a) 3(a) 2(a) 2(b) THEOREM 6(b): x ( x + y ) = x by duality. .

PROOF OF THEOREM 6(a) USING TRUTH TABLE x 0 0 1 1 y 0 1 0 1 xy 0 0 0 1 x + xy 0 0 1 1 .

PROOF OF THEOREM 5(a): (x+y) =xy x 0 0 1 1 y 0 1 0 1 x+y 0 1 1 1 (x+y) 1 0 0 0 x 1 1 0 0 y 1 0 1 0 xy 1 0 0 0 .

OPERATORE PRECEDENCE 1. 2. 3. 4. Parenthesis NOT AND OR .

Boolean function ± described by an algebraic expression consisting of binary variables. and the logic operation symbols. the constants 0 and 1. ± can be transformed from an algebraic expression into a circuit diagram composed of logic gates connected in a particular structure.BOOLEAN FUNCTIONS Boolean algebra an algebra that deals with binary variables and logic operations. ± can be represented in a truth table. . ± expresses the logical relationship between binary variables and is evaluated by determining the binary value of the expression for all possible values of the variables.

The complement operation dictates that when y = 1. y = 0. F1 is equal to 1 if x = 1 or if y = 0 and z = 1. Therefore. F1 is equal to 0 otherwise.EXAMPLE 1: F1 = x + y z F1 is equal to 1 if x is equal to 1 or if both y and z are equal to 1. .

TRUTH TABLE FOR F1 x 0 0 0 0 1 1 1 1 y 0 0 1 1 0 0 1 1 z 0 1 0 1 0 1 0 1 F1 0 1 0 0 1 1 1 1 GATE IMPLEMENTATION OF F1 x y z F1 .

ALGEBRAIC MANIPULATION Implementation of Boolean expression with logic gates: ± each term requires a gate ± each variable within the term designates an input to the gate. 8 literals . in complemented or uncomplemented form. Literal a single variable within a term. ± Example: F = x y z + x yz + xy 3 terms.

x(x +y) = xx +xy = 0+xy = xy x+x y = (x+x )(x+y) = 1(x+y) = x+y (x+y)(x+y ) = x+xy+xy +yy = x(1+y+y ) = x xy+x z+yz = xy+x z+yz(x+x ) = xy+x z+xyz+x yz = xy(1+z)+x z(1+y) = xy+x z (Concensus theorem) 5. 2. .Examples: Simplify the following Boolean functions to a minimum number of literals: 1. 3. (x+y)(x +z)(y+z) = (x+y)(x +z). 4. by duality from function 4 (Consensus theorem).

May be derived algebraically through DeMorgan s Theorems: ± 3-variable form of De-Morgan s theorem: (A+B+C) =(A+x) let B+C=x =Ax by theorem 5(a) = A (B+C) substitute B+C=x = A (B C ) by theorem 5(a) =ABC by theorem 4(b) .COMPLEMENT OF A FUNCTION. F Obtained from changing 0 s to 1 s and 1 s to 0 s in the value of the function F.

. Generalized form of DeMorgan s theorem: ± (A+B+C+D+ +F) = A B C D F ± (ABCD F) = A +B +C +D + +F The generalized form states that the complement of a function is obtained by interchanging AND and OR operators and complementing each literal.

± Answer: F = (x+y +z)(x+y+z ) G = x +yz +y z . Example: ± Find the complement of the functions F = x yz + x y z G = x(y z + yz) Using DeMorgan s theorem.

Example: ± Find the complement of the functions F = x yz + x y z G = x(y z + yz) Using duality ± Answer: Dual of F is (x +y+z )(x +y +z) ± F = (x+y +z)(x+y+z ) Dual of G is x+(y +z )(y+z) ± G = x +yz +y z .

x y .CANONICAL AND STANDARD FORMS MINTERM or STANDARD PRODUCT. a variable is primed if the corresponding bit of the binary number is a 0 and unprimed if a 1. xy . y minterms: x y . ± In each minterm representation. mj ± Represents each of the AND terms that results from the possible combinations of binary variables combined with an AND operation. xy ± n variables can be combined to form 2n minterms ± has the symbol mj where the subscript j denotes the decimal equivalent of the binary number of the minterm designated. variables: x . .

x +y . x+y ± n variables can be combined to form 2n maxterms ± has the symbol Mj where the subscript j denotes the decimal equivalent of the binary number of the maxterm designated. y maxterms: x +y . Mj ± Represents each of the OR terms that results from the possible combinations of binary variables combined with an OR operation. a variable is unprimed if the corresponding bit of the binary number is a 0 and primed if a 1. ± In each maxterm representation. variables: x .CANONICAL AND STANDARD FORMS MAXTERM or STANDARD SUM. . x+y .

MINTERMS AND MAXTERMS FOR THREE BINARY VARIABLES Minterms Maxterms x 0 0 0 0 1 1 1 1 y 0 0 1 1 0 0 1 1 z 0 1 0 1 0 1 0 1 Term xyz xyz x yz x yz xy z xy z xyz xyz Designation m0 m1 m2 m3 m4 m5 m6 m7 Term x+y+z x+y+z x+y +z x+y +z x +y+z x +y+z x +y +z x +y +z Designation M0 M1 M2 M3 M4 M5 M6 M7 .

MINTERMS AND MAXTERMS FOR THREE BINARY VARIABLES variables functions x 0 0 0 0 1 1 1 1 y 0 0 1 1 0 0 1 1 z 0 1 0 1 0 1 0 1 f1 0 1 0 0 1 0 0 1 f2 0 0 0 1 0 1 1 1 .

In SUM OF PRODUCTS (SOP): f1 = x y z + xy z + xyz = m1 + m4 + m7 Complement of f1. f1 : f1 = x y z +x yz +x yz+xy z+xyz by duality: f1 = (x+y+z)(x+y +z)(x+y +z )(x +y+z )(x +y +z) In PRODUCT OF SUMS (POS): f1 = M0 M2 M3 M5 M6 .

f2 : f2 = x y z +x y z+x yz +xy z by duality: f2 = (x+y+z)(x+y+z )(x+y +z)(x +y+z) In PRODUCT OF SUMS (POS): f1 = M0 M1 M2 M4 .In SUM OF PRODUCTS (SOP): f2 = x yz + xy z + xyz +xyz = m3 + m5 + m6 + m7 Complement of f2.

If a term misses one or more variables. If the function is not written as a sum of minterms. we can obtain 2n distinct minterms and any Boolean function can be expressed as a sum of minterms. it can be made so by first expanding the expression into a sum of AND terms. where x is one of the missing variables .CANONICAL FORMS For n variables. it is ANDed with an expression such as x + x .

4. we can use truth table to determine the answer.5.C) = (1.6. Answer: A = ABC+ABC +AB C+AB C B C = AB C+A B C F = ABC+ABC +AB C+AB C +A B C F = A B C + AB C + AB C+ABC +ABC F = m1 + m4 + m5 + m6 + m7 F(A. .CANONICAL FORMS Example: Express the Boolean function F=A+BC As a sum of minterms.7) Also.B.

where x is one of the missing variables . it is ORed with an expression such as xx . Use x+yz = (x+y)(x+z) If a term misses one or more variables.CANONICAL FORMS For n variables. we can also obtain 2n distinct maxterms and any Boolean function can be expressed as a product of maxterms. If the function is not written as a product of maxterms. it can be made so by first writing the expression into a form of OR terms.

2.4. Answer: F = xy+x z =(xy+x )(xy+z) = (x+x )(y+x )(x+z)(y+z) = (y+x )(x+z)(y+z) x +y = x +y +zz =(x +y +z )(x +y +z ) x+z = y+z = F = (x+y+z)(x+y +z)(x +y+z)(x +y+z ) F = M0 M2 M4 M5 F(A.B.5) .C) = (0.CANONICAL FORMS Example: Express the Boolean function F = xy+x z As a product of maxterms.

2.5. That is m j = Mj .3) If we take the complement of F by DeMorgan s theorem.C) = (1.C) = (0.B. the maxterm with subscript j is a complement of the minterm with the same subscript.4. Example If F(A.B.6.CONVERSION BETWEEN CANONICAL FORMS The complement of a function expressed as the sum of minterms equals the sum of minterms missing from the original function.7) Then F (A. we obtain F in a different form: F = ( m0 + m2 + m3 ) = m 0 m 2 m 3 = M0 M2 M3 Therefore.

4.5) .6.B.C) = (0.2.C) = (1. Example If F = xy +x z Then using a truth table we have F(A.7) Since we have three variables Then F (A. interchange the symbol and and list those number missing from the original form .CONVERSION BETWEEN CANONICAL FORMS To convert from one canonical form to another.B.3.